B354 Comparison of intraperitoneal instillation of ropivacaine over ultrasound guided rectus sheath block in laproscopic cholecystecomy: a pilot study. (11th August 2022) - Ramesh, J; Kota, S; Joshi, R; Ramakrishnan, L
Abstract : Background and Aims: Laparoscopic cholecystectomy replaced open surgery as preferred method. The largest component of pain is incisional pain (50 to 70%). Rectus sheath block acts at terminal branches of intercostal nerves in the space between rectus abdominis muscle and posterior rectus sheath resulting in anaesthesia of the midline. While intraperitoneal instillation blocks the visceral nociceptive conduction from area of tissue damage and peritoneum. The aim of this study was to evaluate the efficacy of intraperitoneal instillation versus rectus sheath block using ropivacaine for postoperative pain relief for laparoscopic cholecystectomy. Methods: After written informed consent 30 adult ASA I, II patients were randomised into 3 groups of 10 patients. Group C (control) received only rescue analgesic on pain, Group I (Intraperitoneal instillation) received 0.25% ropivacaine 40 ml before surgery, Group R (Rectus sheath block) received bilateral block with 30 ml of 0.25% ropivacaine before surgery. Primary objective-compare the VAS at 2nd, 4th, 6th, 12th, 24th, 48 hours. Secondary objectives-assess time for 1st rescue analgesia and tramadol consumption in first 6 hours. Results: The demographic data were comparable. VAS scores at various intervals were lower in both group R and group I compared to C ( p-<0.05). VAS in group R was significantly lower than group I (p value <0.05).Total tramadol consumption was lower in group R compared to I and C (p 0.0002). The first rescue analgesia was significantly later in group R (p 0.0005) Conclusions: Pre-emptive administration of rectus sheath block or intraperitoneal instillation of 0.25% ropivacaine provides good postoperative analgesia after laparoscopic cholecystectomy. Rectus sheath block provides superior analgesia than intraperitoneal instillation.